Assessing Time Since Death by using Changes in Electrolytes in C.S.F and Vitreous Humour in Bodies Subjected to Autopsy (Indian Journal of Forensic Medicine & Toxicology, 2022)
Death is an unpredictable truth in every one’s life. Death can be broadly classified as natural and unnatural.Medicolegal experts are concerned only with unnatural deaths. My study was aimed to estimate time since death(TSD). TSD is done grossly using various factors, to narrow down the limit of margin of error I assessed changes inelectrolytes in Cerebro spinal fluid and vitreous humour in bodies subjected to autopsy. The study was conductedon 100 cases brought for medicolegal autopsy. I concluded as there is definite relation in the values of electrolyteswith relation to the post-mortem interval or time since death.
Keywords: Time since death (TSD), Electrolytes, Cerebro spinal fluid (CSF) and vitreous humour (VH).